Comparison of conventional radiograph with low-dose computed tomography of sacroiliac joints in patients with proven sacroiliitis - Sarkar, Rupa; Sen, Debraj (International Journal of Research in Medical Sciences, 2026)
Background: Sacroiliitis is central to diagnosing axial spondyloarthritis (axSpA), yet conventional radiography suffers from anatomical superimposition and low sensitivity for early structural change. Low-dose computed tomography (LDCT) provides cross-sectional detail at a radiation dose comparable to plain radiography. Aim was to evaluate LDCT versus conventional sacroiliac (SI) joint radiography in assessing sacroiliitis. Methods: This prospective, observational, cross-sectional study enrolled 30 consecutive adults with proven sacroiliitis at a tertiary centre. All underwent pelvic radiography (SAPA view) and LDCT of the SI joints (Philips Brilliance iCT 256-slice; 120 kV, 30 mAs; effective dose 1 mSv). Two blinded radiologists independently scored 60 SI joints using a modified European image-quality system covering technical parameters (joint-margin and soft-tissue delineation, superior/inferior visualisation, absence of superimposition) and pathological parameters (joint-space change, erosions, sclerosis, soft-tissue content). Chi-square/Fisher’s exact and unpaired t-tests were used; p<0.05 was significant. Results: Mean age was 33.1±8.7 years; 96.7% were male; axSpA accounted for 90.0% of diagnoses. LDCT was significantly superior to radiography for soft-tissue delineation (98.3% versus 18.3%), superior/inferior joint margins (98.3% versus 55.0%), absence of superimposition (100% versus 36.7%), and iliac-margin erosion detection (86.7% versus 55.0%) (all p<0.001). Mean total imaging score was 7.6±1.3 for LDCT versus 4.3±1.8 for radiography (p<0.001), with consistent superiority across all subgroups; scores correlated strongly (r=0.742, p<0.001). Conclusions: LDCT delivered substantially superior image quality and structural-lesion detection than radiography at a comparable dose and should be integrated into diagnostic algorithms for suspected sacroiliitis, particularly when radiographs are inconclusive.